Contemporary Aspects of Insurance Revenue from Issued Insurance Contracts - Koteva, Nadya (Research Papers, 2024)
This article presents the main changes in the reporting of insurance revenue in connection with issued insurance contracts. Emphasis is placed on insurance revenue in the statement of profits and losses, which, as a result of the introduction of IFRS17 “Insurance contracts”, fundamentally differ from the requirements of the previous standard. The focus of the study is directed to the new moment for separate presentation of the insurance revenue from issued insurance contracts compared to the other revenue from the activity. A comparative analysis of the reporting and presentation of insurance revenue from insurance contracts with the model applicable until the entry into force of IFRS17 “Insurance contracts” was made.